Strategic leniency: insights from game theory and empirical evidence - Jablonskis, Martynas (Vilnius University Open Series, 2020)
Strategic leniency signifies potential exploits of leniency that could generate detrimental effects. Leniency could be exploited in three distinct ways: (1) used to punish cartel deviator; (2) used as a cartel exit strategy; (3) used as a way to report false cartels hoping that rivals will be fined. Strategic leniency has roots in game theory and has been used in theoretical works on leniency. However, it is difficult to verify, whether firms actually conceive leniency strategically. The article addresses the problem by analysis of 42 cartel cases, investigated by the European Commission, throughout the years 2010–2018. We find some support for the strategic leniency, but evidence is more indicative, rather than conclusive. We also find that 2002 leniency reform in the European Union generated no immediate disruptive effect on pre-reform cartels. Besides the article argues for insufficiency of leniency to uncover cartels in a form of concerted practices, and spots a seeming legal gap: there are no legal rules in current Leniency Notice to prevent abuses of leniency. Overall, the success of leniency should not be overstated.